Deformation of DNA during site-specific recombination of bacteriophage lambda: replacement of IHF protein by HU protein or sequence-directed bends. - Goodman, S D (1992)
Escherichia coli IHF protein is a prominent component of bacteriophage lambda integration and excision that binds specifically to DNA. We find that the homologous protein HU, a nonspecific DNA binding protein, can substitute for IHF during excisive recombination of a plasmid containing the prophage attachment sites attL and attR but not during integrative recombination between attP and attB. We have examined whether IHF and HU function in excisive recombination is mediated through DNA bending. Our strategy has been to construct chimeric attachment sites in which IHF binding sites are replaced by an alternative source of DNA deformation. Previously, we demonstrated that properly phased bends can substitute for the binding of IHF at one site in attP. Although this result is highly suggestive of a critical role of IHF-promoted bending in lambda integration, its interpretation is obscured by the continued need for IHF binding to the remaining IHF sites of these constructs. In the present work, we engineered a population of sequence-directed bends in the vicinity of the two essential IHF sites found in attR and attL. Even in the absence of IHF or HU, pairs of these attachment sites with properly phased bends are active for both in vitro and in vivo excision. This success, although tempered by the limited efficiency of these systems, reinforces our interpretation that IHF functions primarily as an architectural element.